ANALISIS PERANAN DAN KEGUNAAN SISTEM INFORMASI AKUNTANSI PADA PT KURNIA EKA NUSA YANG BERBASIS ACCURATE-DEKSTOP - Yuli Meliana; Hwihanus Hwihanus (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
An accounting information system is a collection of resources such as people and equipment that have been set up to manage and transform data into information. Accounting information systems are very important for all companies, both service companies, trading and manufacturing companies. Because besides being useful as a recording of the company's financial statements, it can also find out what the company's development is like every year. This study aims to determine the role and usefulness of the Accounting Information System used in managing financial data so that it is more effective at PT Kurnia Eka Nusa. In a company, the income and expenditure cycle is important. For economic growth, it can be seen from the two cycles. PT Kurnia Eka Nusa is a trading company engaged in industry and. Data collection methods used literature review and library research. The data source used is by conducting interviews with company owners, from an overview of the company, documents used by the company such as sales documents, travel documents, invoices in the company, organizational structure to job desks for each division and guidelines for company procedures regarding income and expenses. accounting information system. This case study shows that sales operations still have some deficiencies and companies can develop an accurate desktop system developed into an accurate online one to maximize system performance.